Incidence of variables non directly controllable by the educational system in students' reading literacy in PISA: a comparative study Spain-Finland - Esteban Vázquez Cano; Eloy López Meneses; Fabrizio Manuel Sirignano (ADIDE Federación, 2014)
This comparative research between Spain and Finland examines the incidence of eight variables of PISA (2012) typologically grouped in three areas: family, internet use for reading activities, and availability of books at home in students' results in reading literacy. Through a descriptive and quantitative methodology, we analyze the incidence of these eight variables in Finnish and Spanish students' reading literacy. The results show that parents' academic and professional level along with the type of book that is available at home are non-significant variables in the development of a high reading literacy; by contrast, the variable that measures Internet use at home for reading news has been highly significant. Finnish students duplicate the Spanish in this variable which increases in 30 points reading literacy results.